The effects of curcumin on hepatic T2*MRI and liver enzymes in patients with β‐thalassemia major: a double‐blind randomized controlled clinical trial - Eghbali, Aziz; Nourigheimasi, Shima; Ghasemi, Ali; Afzal, Roghayeh Rahimi; Ashayeri, Neda; Eghbali, Aygin; Khanzadeh, Shokoufeh; Ghaffari, Kazem (Frontiers in Pharmacology, 2023)
Background: Curcumin present in turmeric has been considered due to its cancer-preventive features, antioxidant and anti-inflammatory properties. This double-blind, randomized, controlled clinical trial with a reasonable sample size and longer intervention period was conducted to investigate how oral curcumin affected cardiac and hepatic T2*MRI and liver enzymes in patients with β‐thalassemia major. Method: This clinical trial study was conducted on 171 patients over 5 years old. The subjects were randomly divided into a curcumin-treatment group and a placebo group to receive either curcumin capsules twice daily or placebo for 6 months. Patients were examined once a month for 6 months to receive capsules and measure the levels of alanine aminotransferase (ALT), aspartate transferase (AST), alkaline phosphatase (ALP), direct and total bilirubin, ferritin and cardiac and hepatic T2*MRI. Result: There was a significant decrease in levels of AST, ALT, ALP, and bilirubin (direct and total) in the curcumin group compared with the placebo group by the end of the study (P < 0.05). The levels of serum ferritin remained unchanged in both groups at the end of the follow‐up period (P > 0.05). No significant differences were observed between the curcumin and placebo groups at baseline values or at the end of the study of cardiac and hepatic T2*MRI and serum magnesium. Conclusions: Administration of curcumin has some beneficial effects on liver function by reducing liver enzymes in patients with beta-thalassemia major.